Mg-Mg bond polarization induced by a superbulky β-diketiminate ligand - Rösch, Bastian; Gentner, Thomas; Eyselein, Jonathan; Friedrich, Alexander; Langer, Jens; Harder, Sjoerd (Chemical Communications, 2020)
The bulk of a recently reported superbulky β-diketiminate ligand was further increased by introducing tBu substituents in the ligand backbone. Attempts to isolate free Mg radicals with this extremely bulky ligand failed. Instead, a dinuclear Mg(i) complex with one chelating and one monodentate β-diketiminate ligand was isolated. Asymmetry in metal coordination results in a polarized Mg-Mg bond.
CRIS-Team Scopus Importer:2020-10-09